Improvement and implementation of the physical development plan for young volleyball players - Yingying, Y. (Theory and Practice of Physical Culture, 2025)
Objective of the study. The subject of the analysis in this paper is the study of the prospects for improving the physical fitness of young volleyball players, taking into account the specifics of their training process.